Sun Tzu and the art of modern warfare - McNeilly, Mark; Sunzi, active 6th century B.C. (New York : Oxford University Press, 2015)
Long acknowledged as a classic text on strategy, Sun Tzu's The Art of War has been admired by leaders as diverse as Mao Zedong and General Norman Schwartzkopf. However, having been written two thousand years ago, the book can be somewhat daunting to the modern reader. Mark McNeilly, author of Sun Tzu and the Art of Business (OUP, 2011), which made Sun Tzu accessible to the business executive, has extracted the six concepts most applicable to modern warfare, making them easy to understand and apply to military situations. Drawing on a wealth of fascinating historical examples, McNeilly shows how these six principles might be used in wars of the future--both conventional wars and terrorist conflicts--and how they can provide insight into current affairs, such as the war on terrorism and China's increasingly important strategic and military role in the world. This updated edition reflects on all that has happened in the past ten years, including the wars in Iraq and Afghanistan, the challenge of Iran, the "Arab Spring," and the continued rise of China. Each chapter includes brand new examples to explain important concepts in The Art of War. Including the full text of The Art of War in the popular translation by Samuel Griffith, with cross-references to quotations used in the book,Sun Tzu and the Art of Modern Warfare unlocks these elusive secrets for anyone interested in strategy and warfare, whether they are professional soldiers, military history buffs, or business executives.
Introduction: the relevance of Sun Tzu to modern warfare -- Win all without fighting: achieving the objective without destroying it -- Avoid strength, attack weakness: striking where the enemy is most vulnerable -- Deception and foreknowledge: winning the information war -- Speed and preparation: moving swiftly to overcome resistance -- Shaping the enemy: preparing the battlefield -- Character-based leadership: leading by example -- Terrorism and the wars in Afghanistan and Iraq: applying Sun Tzu's principles -- Ancient principles for future battlefields: applying Sun Tzu's principles.
Includes bibliographical references (pages 303-306) and index.
Keywords: Sunzi, -- active 6th century B.C.; Military art and science; Military art and science -- Case studies; POLITICAL SCIENCE -- Political Freedom & Security -- International Security; HISTORY -- Military -- Other; Military art and science; Case studies